Investigation of a solar-biomass gasification system with the production of methanol and electricity: Thermodynamic, economic and off-design operation. (1st June 2019) - Bai, Zhang; Liu, Qibin; Gong, Liang; Lei, Jing
Highlights: A solar-driven biomass gasification based polygeneration system is proposed. The system mathematical model of off-design evaluations is developed. The annual thermodynamic performances and transient characteristics are investigated. Implementing the system economic evaluation and cost sensitive analysis. Abstract: A new solar-biomass gasification polygeneration system is developed to efficiently utilize renewable energy in this work, with the production of liquid fuel methanol and electricity. In the system, the collected high-temperature concentrated solar energy with a beam-down optical configuration is used to drive biomass gasification, the cotton stalk is selected as feedstock, and the produced syngas is fed into the reactor for methanol synthesis. The un-reacted syngas and the system waste heat are efficiently utilized via the combined cycle to generate electricity. The designed biomass consumption rate and power capacities are 100 ktons/year and 32.7 MWe, respectively. The thermodynamic and economic performances of this polygeneration system are investigated, and the on-design energy efficiency and the exergy efficiency of the system reach to 51.89% and 51.23%, respectively. According to the off-design evaluation within a typical year, the annual production of methanol and electricity are 54.80 ktons and 50.85 GW·h, respectively. Compared with the reference system which consists of a typical methanol synthesis system with biomass-steam gasification and a solar tower power generation system, the annual averaged efficiency of the proposed solar-biomass polygeneration system is increased to 48.35% from 41.09% of the reference system, and the monthly averaged efficiency is varying in the range of 46.65%–49.05%. In addition, the specific biomass consumption rate is reduced by 27.33%, and the levelized cost of methanol is 361.88 $/ton with reasonable economic competitiveness. The polygeneration system achieves competitive thermodynamic and economic potential, and provides an alternative and promising way for efficiently utilizing abundant solar energy and biomass resources.